1992
DOI: 10.1302/0301-620x.74b5.1527131
|View full text |Cite
|
Sign up to set email alerts
|

Remodelling of angular deformity after femoral shaft fractures in children

Abstract: We reviewed 28 children with unilateral middle-third fractures of the femoral shaft who had an angular deformity after union of 10 degrees to 26 degrees. At an average follow-up of 45 months (20 to 66), we measured remodelling of the proximal physis, the distal physis and the femoral shaft. The average correction was 85% of the initial deformity. We found that 74% of correction occurred at the physes and only 26% at the fracture site. Neither the direction nor the magnitude of the angulation much influenced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
3

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 0 publications
1
49
1
3
Order By: Relevance
“…Most authors see no advantage in prophylactic shortening of the fracture in order to reduce the differences in leg length [8,9,11,12]. Most publications show a leg length discrepancy between 0.5 and 2.5 cm, although an idiopathic factor of 0.7 cm must be taken into consideration [7,17,38]. A study by Kregor et al which [20] included 37 patients with intramedullary nailing, documented a leg length difference in 22% of the cases, with the average difference being more than 5 mm.…”
Section: Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Most authors see no advantage in prophylactic shortening of the fracture in order to reduce the differences in leg length [8,9,11,12]. Most publications show a leg length discrepancy between 0.5 and 2.5 cm, although an idiopathic factor of 0.7 cm must be taken into consideration [7,17,38]. A study by Kregor et al which [20] included 37 patients with intramedullary nailing, documented a leg length difference in 22% of the cases, with the average difference being more than 5 mm.…”
Section: Effectivenessmentioning
confidence: 99%
“…All documented malangulations were less than 15°a nd, according to the literature, clinically irrelevant [27,28,32,38]. Wallace et al [38] showed a correction in 85% of the patients with 10°-angulation or more and came to the conclusion that a malangulation of 25°had enough corrective potential to prevent a shift of the joint axis.…”
Section: Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of remodelling occurs by reorientation of the growth plates. Asymmetrical and longitudinal growth of the physis contribute to it [9]. Remodelling capacity depends on the number of years of growth remaining ahead, the proximity of the fracture to a rapidly growing physis, the magnitude of angular deformity, and the plane of angulation relative to adjacent joints.…”
Section: Physiological Featuresmentioning
confidence: 99%
“…In this respect, internal fixation is more certain to achieve an acceptable reduction than either external fixation or splintage. Long-term reviews of remodelling such as that of Wallace and Hoffman 2 show that an initial angular deformity of even 25° can recover to give normal function. Overgrowth is more likely after an operation, although the importance of length discrepancy may have been overrated unless it reaches 2 cm or more.…”
Section: Fracture Of the Femur In Childrenmentioning
confidence: 99%